Surfactants and Detergents - Kumar Dutta, Ashim (IntechOpen, 2019)
Surfactants by virtue of their structure form self-assembled organized structures that exhibit fascinating properties useful for a wide range of applications. This book is a compilation of chapters from leading experts highlighting the use of specific surfactants and their functional properties in new and emerging areas of science and technology. The first two chapters of this book discuss the various applications of surfactants, including their use in cosmetics, oil recovery from rocks and mineral processing. Subsequent chapters cover advanced topics like new-generation polymer-based nanoparticles with microbial activity and complex phase systems formed as a result of charge-induced interactions between surfactants, polymers and proteins with potential applications in medical devices. In addition, this book reports for the first time on bio-surfactants extracted from micro-organisms present in the clouds. This report is not the only one of its kind, but it opens up a totally new area of research in terms of an unexplored source of bio-surfactants. It also paves the way for understanding their role in controlling our atmosphere and climate.